2009
DOI: 10.2355/isijinternational.49.1474
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Flux Dissolution in Oxygen Steelmaking

Abstract: Based on the previous studies, when lime dissolves in silica containing slag, a film of dicalcium silicate, 1474© 2009 ISIJ ISIJ International, Vol. 49 (2009), No. 10, pp. 1474-1482 Kinetics of Flux Dissolution in Oxygen SteelmakingNeslihan DOGAN, Geoffrey A. BROOKS and Muhammad Akbar RHAMDHANI A mathematical model has been developed to predict the dissolution rate of added fluxes such as lime and dolomite as a sub-model of an overall kinetic model of top-blown oxygen steelmaking process. The calculation of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 27 publications
0
47
0
4
Order By: Relevance
“…4) The observed drop in the equilibrium concentration of CaO in the slag samples with the increasing content of MgO in lime can be explained by an increase in (Mg, Fe and Ca) silicates and magnesiowustite concentration in the volume of lime, which as a consequence, further complicates the process of lime dissolution. 4,8,15,17) Figure 8 shows microscopic raster images (SEM Tesla XRAY Oxford) of lime containing 4.3, 7.6 and 80% MgO, after 5 minutes of immersion in the melt at 1 500°C, and the phase composition of samples carried out with a powder diffractometer "Bruker D2 Phaser". Sample containing 80% of magnesium oxide was prepared by Voestalpine Stahl Linz consisting of periclase (MgO) and portlandite (Ca(OH) 2 ) phases.…”
Section: The Calculation Of the Diffusion Coefficients Of Lime Dissolmentioning
confidence: 99%
See 2 more Smart Citations
“…4) The observed drop in the equilibrium concentration of CaO in the slag samples with the increasing content of MgO in lime can be explained by an increase in (Mg, Fe and Ca) silicates and magnesiowustite concentration in the volume of lime, which as a consequence, further complicates the process of lime dissolution. 4,8,15,17) Figure 8 shows microscopic raster images (SEM Tesla XRAY Oxford) of lime containing 4.3, 7.6 and 80% MgO, after 5 minutes of immersion in the melt at 1 500°C, and the phase composition of samples carried out with a powder diffractometer "Bruker D2 Phaser". Sample containing 80% of magnesium oxide was prepared by Voestalpine Stahl Linz consisting of periclase (MgO) and portlandite (Ca(OH) 2 ) phases.…”
Section: The Calculation Of the Diffusion Coefficients Of Lime Dissolmentioning
confidence: 99%
“…The increase in the concentration of MgO in lime slows down the dissolution rate of the samples. In the work 4,15) authors measured the rate of calcined dolomite samples СаСО 3 ·MgCO 3 dissolution in the slag with the composition FexO-CaO-SiO 2 , containing FeO from 20 to 65%. Authors suggested a limitation of the MgO diffusion in the slag containing FeO more than 20% through the surface layer at the interface.…”
Section: Determination Of Lime Mass Transfer Coefficients In the Modementioning
confidence: 99%
See 1 more Smart Citation
“…Over these ten years, a lot of research has been conducted with dynamic tests, [26][27][28][29]32) stagnant tests, [33][34][35] theoretical modelling, 36) and process simulation to consider the slagging behavior. 37,38) This indicates that the dissolution of lime is still one of the unsolved subjects in steelmaking reactions.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…The calculation procedure of physical properties of slag was provided in the previous publication. 34) Droplet generation was then calculated as a function of blowing conditions as explained elsewhere. 35) The output results of droplet generation submodel were used to calculate the initial velocity of metal droplets ejected to the emulsion phase and to calculate the quantity of metal droplets ejected.…”
Section: Formulation Of the Modelmentioning
confidence: 99%